Video Surveillance Using Adaptive-Rate Compressive Sensing (International Journal of Engineering and Computer Science, 2017)
We provide a novel adaptive rate compressive sensing technique for video surveillance with the use of side information .This method exploits the advantages of low resolution information of an image. Unlike the current compressive sensing techniques we consider the upper bound on the number of significant coefficients which contains the image in the video sequence to be unknown. We develop our method based on background subtraction using single pixel camera. For each image in the video sequence the proposed technique assign a set of compressive sensing measurements to adjust from image to image